Seasonal fluctuations in pollen concentrations of allergenic taxa in the air of Poznań in 2004 - Stach, Alicja; Baena, Jose Carlos Prieto (Biodiversity: Research and Conservation, 2006)
A pollen calendar of selected allergenic taxa in the air of Poznań in 2004 has been prepared and addressed to allergologists and allergic patients in the Wielkopolska region. The calendar was based on 11 tree taxa and 7 taxa of herbaceous plants. Analysis of the taxa in the study year revealed that pollen of trees was predominant in the air. The peculiar character of 2004 was that Corylus and Alnus started flowering almost two months earlier than year before. Patients allergic to Corylus and Alnus were likely to be at risk of allergenic reaction from February. The pollen seasons of later flowering trees and herbaceous plants began only a few days earlier compared to the previous year. Patients allergic to pollen allergens of herbaceous plants were at risk from the second decade of May to the end of August.